The Influence Of Leadership Styles And Innovation Culture On Employee Creativity Level In Continuous Improvement Program Cycle At Pertamina Hulu Rokan - Grahan Rizka Pradita; Henndy Ginting (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Pertamina Hulu Rokan is a new entity in the Upstream Subholding, Pertamina Hulu Energi which has a working area on the island of Sumatra. Most of its working area is in Pekanbaru, which is the work area of Ex. Chevron Pacific Indonesia (CPI). Pertamina Hulu Rokan is faced with the challenge of oil and gas production that must be sustained to maintain production sustainability. Continuous Innovation activities are activities that are routinely carried out by workers at Pertamina Hulu Rokan. This culture of innovation has taken place to maintain the performance of oil and gas production activities. The Innovation Culture that was formed was the Continuous Improvement Program (CIP). Every worker in the Zone 1, Zone 4, and Rokan Zone work areas makes innovations to produce value creation that is beneficial for the company in terms of revenue growth, cost saving, and cost avoidance. The number of innovations produced by workers is not always the same, and some do not exceed the innovation target set by the company. The role of leadership styles in the implementation of innovation culture is urgently needed as a role model for workers in making innovations independently. This study uses a quantitative approach, namely by conducting a questionnaire with variables Transformational Leadership, Transactional Leadership, Creativity, and Culture Innovation. The distribution of questionnaires was carried out thoroughly to workers from various functions located in the work areas of Head Office, Zone 1, Zone 4, and Rokan Zone. The results of the questionnaire were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) to find out and evaluate which variables are significant and have the greatest influence on the management of innovation culture in PHR today. This research focuses on the most dominant Leadership Style so that the right strategies and solutions can be identified to increase the number of innovations with the aim of increasing value creation for the company. The results of this study show that Tranformational Leadership and Transactional Leadership have a significant impact on the culture of innovation, but Transfromational has a significant impact on the culture of innovation.